2017
DOI: 10.3892/etm.2017.4909
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture with lung cancer A549 cells promotes the proliferation and migration of mesenchymal stem cells derived from bone marrow

Abstract: The initiation and progression of various types of tumors, such as lung neoplasms, are driven by a population of cells with stem cell properties and their microenvironment. Bone marrow mesenchymal stem cells (BM-MSCs) in long-term in vitro culture may exhibit spontaneous changes in stem cell biological properties, including malignant transformations; however, the molecular mechanisms of this have not been fully elucidated. In the present study, a BM-MSC and lung cancer A549 cell co-culture system was utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…However, exosomes produced by tumor cells are capable of influencing MSCs [28, 29]. MSCs are reportedly intimately associated with tumor cells in the tumor microenvironment; indeed, co-culture with lung cancer A549 cells promoted the proliferation and migration of hBMSCs, likely by modulating the expression of genes related to the ERK signaling pathway [30]. Furthermore, C6 glioma-conditioned medium induced a tumor-like phenotype in MSCs, possibly in a manner involving the S100B/RAGE pathway [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, exosomes produced by tumor cells are capable of influencing MSCs [28, 29]. MSCs are reportedly intimately associated with tumor cells in the tumor microenvironment; indeed, co-culture with lung cancer A549 cells promoted the proliferation and migration of hBMSCs, likely by modulating the expression of genes related to the ERK signaling pathway [30]. Furthermore, C6 glioma-conditioned medium induced a tumor-like phenotype in MSCs, possibly in a manner involving the S100B/RAGE pathway [31].…”
Section: Discussionmentioning
confidence: 99%
“…The present in vitro study included four groups of cells, A549 lung cancer cells, untreated bone marrow-derived MSCs, untreated bone marrow-derived MSCs co-cultured with A549 cells (Co-BMSCs), and co-cultured bone marrow-derived MSCs and A549 cells treated with 50 μg/ml of Astragalus polysaccharide (APS) (Co-BMSCs + APS). In a previous study, we reported that Co-BMSCs showed a high rate of proliferation and abnormal changes in morphology, which are findings supported by those of the present study [32]. Previous studies have shown that lung tumor exosomes initiated changes in long non-coding RNA (lncRNA) [15], and induced a pro-inflammatory phenotype of MSCs via the nuclear factor-kappaB (NF-κB) and Toll-like Receptor (TLR) signaling pathways [14].…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that MSCs can be recruited to tumors and participate in the formation of the tumor stroma [ 43 47 ]. Recent studies have shown that MSCs can undergo malignant transformation when they are cultured for a long period of time or in a tumor-like environment, although the underlying mechanism remains unknown [ 10 , 30 , 48 , 49 ]. In this study, we induced MSCs to undergo malignant transformation by indirectly coculturing them with C6 glioma cells.…”
Section: Discussionmentioning
confidence: 99%